Credit guarantee schemes: Are they efficient? Experience from European Union countries - Halina Waniak Michalak; Maciej Woźniak; Robert Lisowski (Comparative Economic Research. Central and Eastern Europe, 2022)
The paper aims to assess selected elements of the business models of credit guarantee schemes (CGSs) implemented in 20 European Union countries within the financial framework between 2007 and 2013. This paper focuses on the CGSs' financial additionality that depends mainly on how these programs are managed, the institutions implementing them, the objectives set and their distribution constraints. We analyse the implementation costs and the use of the funds allocated to implement the schemes. To reach the goal, we used several methods: the Kruskal-Wallis by ranks, the median test, discriminant analysis, multidimensional scaling, and correlation. We also did the power analysis. We discovered that the efficiency of CGS implemented by non-governmental organisations, mutual guarantee funds and regional agencies is related to the level of regional development. The relationship is not visible only when banks are engaged, which may be due to the impossibility of assigning a bank's activities to a single region. However, we did not find differences in efficiency between types of organisations that implement CGSs. The answers to the research questions posed in the article can help policymakers and researchers conclude whether it is cost-effective to continue supporting CGSs and whether the management of these schemes should change. The paper contributes to the economic policy theory in the area of state aid to SMEs and public finance.
Keywords: G21; G23; G28; M21; 330; credit guarantee schemes; business model; European Union; efficiency; non-governmental organisations; small and medium enterprises